Optimization Of Minimum Consumption Durations For Stunting Toddler In An Effort To Overcome Stunting Using Linear Program - Hasanah, Nur; Ambarsari, Ida Fitriana; Astindari, Tri; Nuryami, Nuryami; Fadia, Virotun Nisaul (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2024)
Stunting is a serious problem in Indonesia. One of the factors that there are still many stunted toddlers in Tlogosari village, Sumbermalang, Situbondo, is the lack of knowledge in the community, especially teenagers, about the importance of maintaining a balanced nutritional diet and the old-fashioned way of thinking about wanting to get their daughters married immediately. This research activity aims to overcome and reduce the problem of stunting in Tlogosari village, Sumbermalang, Situbondo. By holding socialization regarding balanced nutrition and making processed Arema foods such as spinach, Moringa leaves and peanuts, it is hoped that this can be a solution for the samples in this study, namely toddlers aged 1-2 years. From research using linear programming calculations, with the brach and bound method, it was obtained that P1 (Arem-arem spinach) = 1, P2 (Arem-arem moringa) = 1, P3 (Arem areem peanuts) = 1 with the duration that stunted toddlers need to To overcome this problem, it was found that it takes 74 days for a stunted toddler to consume 1 spinach fruit, 1 moringa fruit and 1 peanut tree every day to avoid the problem of stunting.